Стенли Харакас и почетоците на православната биоетика - Stefan Gogovski (ПБФ „Свети Климент Охридски“ - Скопје, 2018)
The study elaborates on the beginnings of Orthodox Bioethics, her thoughts, teachings, principles, position, methods, and development, through the elaboration of its fundamental roots planted by fr. Stanley Samuel Harakas (1932-), historically recognized as the first orthodox bioethicist. The research itself intends to offer one academic theological reflection, at the same time providing an orthodox moral study concerning the ecclesial life of the Orthodox faith, together with its general structure. It is an attempt to deliver a clean elaboration of the moral principles as a way of life inside the Christian community, thanks to whom the bioethical thought was born and applied in a health care contest from an orthodox perspective for preserving the dignity of the person and the life as a precious gift from God.